2009
DOI: 10.1080/00071660903317571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal corticosterone treatment on incubation length of eggs laid by Japanese quail hens selected for divergent adrenocortical stress responsiveness

Abstract: 1. Previous studies have shown that more yolk corticosterone is found in the eggs of random bred Japanese quail hens implanted with corticosterone during egg formation; both unstressed and stressed quail hens selected for exaggerated (high stress) rather than reduced (low stress) plasma corticosterone response to brief restraint deposit more corticosterone into their egg yolks. The length of egg incubation is also known to be shorter in eggs laid by high than low stress hens. 2. Here we investigated the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…At this point, we may only speculate why the expected negative association between CORT reactivity and reproductive success is dissipated in females facing a high risk of predation. Longer incubation periods under high predation risk may increase clutch predation risk (Martin & Schwabl, ), an effect that could be counterbalanced by elevated maternal CORTs speeding up the rate of embryonic development (Schmidt et al ., ). Perhaps in line with this argument, shy eider females having longer flight initiation distances had an abbreviated incubation period (Seltmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…At this point, we may only speculate why the expected negative association between CORT reactivity and reproductive success is dissipated in females facing a high risk of predation. Longer incubation periods under high predation risk may increase clutch predation risk (Martin & Schwabl, ), an effect that could be counterbalanced by elevated maternal CORTs speeding up the rate of embryonic development (Schmidt et al ., ). Perhaps in line with this argument, shy eider females having longer flight initiation distances had an abbreviated incubation period (Seltmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In particular stress hormones and sex hormones are well known to exert large effects on the developing brain [41]. Similar to the thyroid hormones, corticosterone (CORT) has been implicated in the timing of hatching [42], and higher CORT levels might lead to earlier hatching [43]. Furthermore, CORT is one of the most well studied hormones in relation to effects of prenatal exposure on behavior [28], and it has been shown that prenatal treatment with CORT caused male chickens to be less aggressive and more prone to being pecked in comparison with controls, while no effect was seen in females [44].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of embryogenesis period arises as a result of selection for the trait of stress resistance in quails, particularly young L + hatch 3.7 hours earlier than L  [47]. This was confirmed in experiments with implantation of empty (control) and containing corticosterone implants (experiment) with L  (control) 397.8±0.5 hours > L  (experiment) 395.9±0.7 hours > L + (control) 393.8±0.3 hours > L + (experiment) 391.2±0.4 hours [48].…”
Section: Features Of Embryogenesis In Meat Hens Genotypes With Differmentioning
confidence: 54%
“…Selection for FP traits determines the differentiation of livestock related to the degree of sympathicoadrenal system (SA) and HPA reactivity. Selection for the increase in stress reactivity results in a reduced embryogenesis period [47,48]. The positive effect of hen selection for FP reduction causes the deterioration of egg quality [58].…”
Section: Features Of Embryogenesis In Meat Hens Genotypes With Differmentioning
confidence: 99%